Causal categories in discourse and cognition - Sanders, Ted, 1963-; Sweetser, Eve (Cognitive linguistics research, 2009)
All languages of the world provide their speakers with linguistic means to express causal relations in discourse. The book discusses parameters of categorization that shape the use of causal connectives and auxiliary verbs across languages like English, Dutch and Polish. Convergence of linguistic, corpus-linguistic and psycholinguistic methodologies appears crucial in determining cognitive categories of causality.